Landscape Map of the Russian Arctic Coastal Zone, Version 1 - National Snow and Ice Data Center (National Snow and Ice Data Center (NSIDC))
The map consists of ESRI Shapefiles of landscape polygons (in landscape unit types) for the Russian Arctic coastal zone (scale 1:4, 000, 000). The map is based on a digital circumpolar Lambert projection map. Polygons have a single attribute (LAND-ID). LAND-ID is an eight-character code that describes the landscape unit. The first two digits code zone, the third and fourth code landscape, the fifth through seventh code lithology, and the eighth codes substrate chemistry. The code is described in detail in an accompanying legend. Large polygons enclosing islands, or continental land areas between major rivers, form the boundaries of many smaller landscape polygons. These large enclosing polygons have LAND-ID values of 0. Some smaller islands (e.g., Zemlya Frantsa) have no codes associated with them. Areas on the far eastern portion of the map also have no code.